The Development of Alginate/Ag NPs/Caffeic Acid Composite Membranes as Adsorbents for Water Purification - Angela Spoială; Cornelia-Ioana Ilie; Georgiana Dolete; Gabriela Petrișor; Roxana-Doina Trușcă; Ludmila Motelica; Denisa Ficai; Anton Ficai; Ovidiu-Cristian Oprea; Mara-Lia Dițu (Membranes, 2023)
Since the water pollution problem still affects the environmental system and human health, the need to develop innovative membranes has become imperious. Lately, researchers have focused on developing novel materials to help diminish the contamination problem. The aim of present research was to obtain innovative adsorbent composite membranes based on a biodegradable polymer, alginate, to remove toxic pollutants. Of all pollutants, lead was chosen due to its high toxicity. The composite membranes were successfully obtained through a direct casting method. The silver nanoparticles (Ag NPs) and caffeic acid (CA) from the composite membranes were kept at low concentrations, which proved enough to bestow antimicrobial activity to the alginate membrane. The obtained composite membranes were characterised by Fourier transform infrared spectroscopy and microscopy (FTIR), scanning electron microscopy (SEM), and thermogravimetric analysis (TG-DSC). Swelling behaviour, lead ion (Pb2+) removal capacity, regeneration and reusability were also determined. Further, the antimicrobial activity was tested against selected pathogenic strains (S. aureus, E. faecalis sp., P. aeruginosa, E. coli and C. albicans). The presence of Ag NPs and CA improves the antimicrobial activity of the newly developed membranes. Overall, the composite membranes are suitable for complex water treatment (removal of heavy metal ions and antimicrobial treatment).